Investigation of charge and discharge regimes of nanomodified heat-accumulating materials - Shchegolkov, Alexander; Schegolkov, Alexey; Karpus, Nikolay; Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2017)
Charge/discharge regimes of nanomodified paraffins have been studied. The nanomodification of paraffin was carried out by using the “Taunit” series nanomaterials with different morphological parameters under ultrasonic treatment. Comparative studies of thermophysical parameters (thermal conductivity and heat capacity) have been conducted for the prepared samples. Under charge/discharge regimes, the effect of “tracking thermal contact” manifests. The thermal conductivity increases to 0.48, 0.42 and 0.36 W/mºС in case of CNM-MD, CNM-M and CNM, relative to the initial thermal conductivity of 0.25 w/mºС. It has been established that the extreme on the thermal dependency graph depends on heat capacity ((57, 63 and 72 ºС for CNM, CNM-M and CNM-MD correspondingly). Modification of paraffin with carbon nanotubes allows controlling the phase-transition parameters, which allows obtaining a variety of temperature dependencies of heat capacity, thermal conductivity and physical-mechanical characteristics by combining different ratios of the “Taunit” series nanotubes and physical influences such as thermal fields and ultrasound. The heat-accumulating materials prepared in such a way allow achieving optimized operation of the heat accumulator under different temperature regimes.